A Minimalist Perspective of Interrogatives in the Punjabi Language - Ahmed, Hafiz Nauman; Hanif, Iqra; Aqeel, Asim (Journal of Communication and Cultural Trends, 2023)
Chomsky’s Theory of Universal Grammar (UG) (1993, 1995) incorporates some universal principles for grammatical descriptions of all possible human languages. It is because all aspects of human languages may not be universal; this theory also offers some parameters through which languages may vary from one to another. The Minimalist Program (MP) (Chomsky, 1993) as a part of UG follows minimalist principles such as the principle of economy, the principle of uniformity, and the search for simplicity, which guide the creation of grammatical rules and representations. The current study analysed the interrogative sentences in Punjabi to determine the similarities between Punjabi and English by using the Minimalist Program (MP) as a theoretical framework. Almost all Punjabi dialects or Standard Punjabi published in the academic context provide many ways to express interrogation. Two common types of interrogative sentences analysed here include yes-no questions and wh-questions which are also called k-questions in Punjabi because they start with a k sound, for instance, kitthe (where), kinj (how), kaunN (why), kii (what), etc, have been analysed. The analysis showed that there is no obligatory movement, either in the case of yes-no questions or in wh-movement in Punjabi, such as in English. Similarly, unlike English, there is neither the movement of auxiliaries nor of any other word in any interrogative sentence. Furthermore, the study concluded that the analysis of the Punjabi language through minimalism is possible and, therefore, it is implied that Punjabi follows the proposed principle of Universal Grammar.